Characteristics of childhood anaphylaxis in different age groups - Celiksoy, Mehmet Halil; Ulas, Selami; Turan, Isılay; Yıldırım, Ilke; Turkyilmaz Ucar, Ozge; Al, Serdar (Allergologia et Immunopathologia, 2024)
Background: Anaphylaxis is a severe systemic hypersensitivity reaction that usually has a rapid onset and can be fatal. Presentations of childhood anaphylaxis vary widely in accordance with the triggers and the patient’s age, geographical region and dietary and lifestyle habits.Methods: The medical records of 177 paediatric patients diagnosed with anaphylaxis between January 2021 and January 2024, whose disease progression was monitored at a single tertiary care centre, were reviewed retrospectively.Results: The study included 177 patients diagnosed with anaphylaxis (107 males and 70 females with a median age of 48 months). The most common allergen responsible was food (53.7%). Egg allergy was the most common source of anaphylaxis, afflicting 35 patients (19.3%), while beta-lactam provoked the most common drug allergy, affecting 24 patients (13.6%). The most common organ involved was the skin (92.7%). When the patients were analysed by age group, there were more males in the infancy, preschool and school age groups, while there were more females in the adolescent group (p = 0.44). Food-induced anaphylaxis became less common with increasing age, whereas the rate of drug-induced anaphylaxis increased (p = 0.01 and p = 0.01, respectively). Cardiovascular system findings were observed more frequently in adolescents compared to other age groups (p = 0.003). Most cases stemming from a food allergy were mild, whereas most drug-induced cases were moderate or severe (p < 0.05). When severity was analysed by age group, mild cases in infants were more common than moderate to severe cases.Conclusion: The aetiological and clinical manifestations of childhood anaphylaxis vary among different age groups.